Exploring structures of product costing systems adopted by Sri Lankan listed companies: focusing on traditional vs. activity based costing systems - Indrani, M.W.; Wickremasinghe, G.; Naidoo, Muthusamy (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
As the business environment has been changing continuously, it is critical to ensure that an appropriate MA system is adopted in organizations for intended purposes. The main objective of this study is to investigate patterns of adopting management accounting (MA) techniques by Sri Lankan listed companies for product costing purposes. This study applies Mixed Method Research approach. Accordingly, data were collected from 42 listed companies representing five industry sectors in Sri Lanka: Food Beverages & Tobacco, Chemicals & Pharmaceuticals, Diversified Holdings, Manufacturing, and Plantation, through interviews and discussions supplementary to the survey. The main tools of analysis for quantitative data were frequency tables, Pie charts, bar charts and Fisher’s exact tests using SPSS software, and thematic analysis and content analysis for descriptive data. The findings suggest that Traditional Costing (TC) systems are still popular among all selected industry sectors/companies except for Plantation sector who apply TC by 25% of companies, as they all apply ABC instead. Considering multiple costing systems, the most popular combination is the application of TC with an activity based costing (ABC) system, as complements or alternatives to one another. The study concludes that listed companies are satisfied with the MA techniques adopted for product costing as either single or multiple systems, regardless of whether they are traditional or modern techniques. Even though Sri Lankan listed companies are functioning with sufficient resources and well-equipped staff that require adoption of modern MA techniques i.e. ABC, most reveal that they still see no need to adopt such techniques because they are satisfied with existing systems and applications.
Keywords: Management accounting techniques; Product costing; ABC systems; listed companies; Industry sectors